A Study on Customer Satisfaction towards in Health Drinks in Theni District - Mahalakshmi, G.; Devi, M. Anusuya (International Research Journal of Management, IT & Social Sciences, 2018)
This research is mainly dealt with the mindset of the consumers buying health drinks. The study on the Brand Loyalty on Consumer Health Drink explains the Taste, Preference. Essential also of the consumers consuming health drinks in their day to day life. This research also focuses on the changing preference of the customers because, in todayâs time, there are much more options in choosing the health drinks according to the consumers taste. To increase the customerâs satisfaction, marketers have developed various marketing programs.